(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Cytoreductive surgery plays a crucial role in the management of ovarian cancer, which remains one of the most lethal gynecologic malignancies worldwide. The primary goal of this surgical procedure is to remove as much visible tumor as possible, thereby improving the effectiveness of subsequent chemotherapy and overall patient survival. Numerous studies have demonstrated that the extent of cytoreduction strongly correlates with prognosis, making surgical expertise and timing essential factors in treatment success. This paper explores the significance, techniques, and outcomes of cytoreductive surgery in ovarian cancer treatment, emphasizing its impact on disease progression and survival rates.